Dual-modal overcoming of physical barriers for improved photodynamic cancer therapy via soft organosilica nanocapsules - Wei Lu; Yang Li; Xiaojun Zhang; Ning Wang; Dong Chen; Yatong Zhao; Guang Li; Xuzhi Shi; Xiaobo Ma; Xiaodan Su; Feng Wang; Chuqiang Shu; et al. (Journal of Nanobiotechnology)
Abstract Amidst the burgeoning field of cancer nanomedicine, dense extracellular matrices and anomalous vascular structures in the tumor microenvironment (TME) present substantial physical barriers to effective therapeutic delivery. These physical barriers hinder the optimal bioavailability of nanomedicine. Here, we propose a pioneering dual-modal strategy for overcoming physical barriers via soft organosilica nanocapsules (SMONs). Hyaluronidase-modified flexible spheres work by degrading the extracellular matrix and utilizing their flexible characteristics to enhance penetration into deeper layers. Compared with their stiff counterparts, the SMONs show diminished Young’s modulus, then the inherent softness of the SMONs confers distinct advantages, and significantly augmented cellular internalization within 4T1 cells, leading to an amplified in vitro photodynamic therapeutic effect. Furthermore, hyaluronidase-functionalized SMONs (SMONs-HAase) exhibit enhanced tumor penetration in 3D spheroids. Post incorporation of the photosensitizer chlorin e6, when administered intravenously, these soft organosilica nanocapsules amplify the efficacy of photodynamic therapy. In addition, RNA-seq analysis of SMONs-HAase-Ce6 shows it alters gene expression, degrading the extracellular matrix and impairing mitochondrial function. To sum up, this work elucidates the potential of a dual-modal strategy, highlighting the promise of SMONs in overcoming TME physical barriers and optimizing therapeutic outcomes. Graphical abstract